Anarcho-capitalist libertarianism: the destruction of the State as a principle of the negation of the common good - Arias Monge, Luis Fabián (2026)
The following research paper aims to conduct a critical study of the relationship between libertarianism and State. Libertarianism is constituted like a life organizational project that seeks to radicalize the market position into society. In order to achieve this objective one of the foundational assumptions of the libertarian theoretical-ideological doctrine is the State total abolition. The anarcho-capitalist principle of libertarianism aspires to a radical transformation of society through a way of life where individual freedom prevails – freedom that, according to their principal theorist is violated by the State. The guiding questions of the discussion are: What are the theoretical foundations of libertarianism? What does the libertarian anarcho-capitalist principle consist of? And if it is possible to project a way of life in which State doesn’t exist? The study is structured around a critical reflection of the scope and dimensions of libertarianism. The article’s main objective it’s to describe the theoretical foundations that constitute the libertarian project. The specific objectives are: a) to examine the assumptions underpinning the strategic alliance between libertarians and the far right; b) to identify the political action strategies promoted by these sectors; c) to analyze the organizational/organic structure of the project; and d) to present key elements of Javier Milei’s libertarian government experience. Describing the foundational assumptions of libertarianism will allow to problematize the relationship between the far-right theoretical-ideological approach and the State. The findings of the research will show that the anarcho-capitalist principle -absolute abolition of the State- embedded in the libertarian reasoning radicalizes a life organization project grounded in the negation of the common good.